USE OF ELECTRONIC EVIDENCE IN THE PROTECTION OF THE MEDICINE - Ховпун, Олексій Сергійович; Муляр, Галина Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: in the scientific article the possibility of a legal right of a person to protect his interests by means of a civil claim in court in order to protect medical secret is investigated. Particular attention is paid to the use of electronic evidence in claims for the protection of medical secrets and discloses the role of the use of electronic evidence as a means of proving the subject of a dispute regarding the restoration of violated law in the field of medical secrecy. Methods of research: in the scientific article used general scientific and special methods of research. Results: the concept of «electronic evidence» as a novelty of civil procedural legislation was considered and their use in civil claims for the restoration of the violated right to medical secret was determined. Discussion: finding ways to improve the mechanism for using electronic evidence in lawsuits to protect medical secrets. Changes to the civil procedure law followed by short stories regarding the application to the court and the provision of electronic evidence for its confirmation. Appeal to a court in order to protect human rights and freedoms is a public instrument, the observance of which is guaranted by the norms of national legislation. Such an appeal is a means of protection, and therefore requires proper legal regulation by the state. Due to the constant changes in the information environment, the improvement of information technology raises the question of consolidating the evidence obtained in the information space. It is such a kind of evidence that electronic evidence is an electronic (digital) form of information, and it contains facts relevant to the case. One of the types of civil actions is a lawsuit to protect violated rights in the health sector: on the fact of disclosure of medical secrets. Medical secret information includes information about a medical examination, an overview and its results, an intimate and family aspect of life. The court faces an important task in researching and evaluating such varieties of evidence as electronic ones. The need to properly investigate electronic evidence and distinguish true from forgery can only a specialist who possesses the necessary knowledge in this field. In addition, the question arises as to how to determine the original document and, accordingly, a copy of it. In case of impossibility to submit evidence, including electronic, the plaintiff must inform the court about this, indicating that this is evidence and the objective reasons for not submitting it in due time. One of the innovations is the statement of the plaintiff regarding the submission of only one statement of claim on this fact and on the specified issues. At present, the lawsuit and evidence must be prepared more thoroughly than before. Electronic evidence can considered correspondence received through social networks Instagram, Facebook, etc.; via Telegram, WhatsApp, Messenger, etc.; correspondence by e-mail; printouts of Internet pages; publications in social networks, etc.